Petrological and Geochemical Characteristics of the Ponostama Ultramafic Intrusion, Sodankylä, Northern Finland - Mäkimattila, Otso (Helsingfors universitet, 2015)
The Ponostama ultramafic intrusion, located within the Central Lapland Greenstone Belt, comprises of pyroxenitic, olivine pyroxenitic and peridotitic units that were emplaced stratiformally between Sodankylä Group tuffs and epiclastics. The intrusion, previously unknown on geological maps, is located in an area of known magmatic sulfide deposits and is Ni-depleted, which indicates prospectivity. Petrographic, geochemical and thermodynamic methods were used to geologically describe the intrusion. In addition Kevitsa Ni-Cu deposit and seven other un-mineralized ultramafic occurrences from CLGB were used as a reference group to compile a mineralogical and trace element comparison and to evaluate ore potential. Cumulate texture is abundant in Ponostoma and a common silicate mineral assemblage consists of tremolite, serpentine, chlorite and variable amounts of primary or metamorphic olivine. Amhibolite facies recrystallization has locally produced poikiloblastic olivine porhphyroblasts. Pseudosection indicates a minimum temperature of 450 °C and low H2O activity for metamorphic olivine growth. Major element compositions have little variation within lithological units and Mg# varies between 70 and 80. Olivine compositions vary between Fo60 and Fo70, which indicates relatively evolved parent magma composition. Metamorphic olivines are less magnesian than primary olivines, but no other compositional differences occur. The Ni and Cu concentrations are similar to un-mineralized host rocks of the Kevitsa deposit due to formation of a sulfide liquid. Immobile trace element concentrations are close to values of the 2.2 Ga Taljavaara intrusion. Low sulfide content together with low Ni and Fo in olivine indicate low ore potential. Ponostaman ultramafinen intruusio sijaitsee Keski-Lapin vihreäkivivyöhykkeellä ja koostuu pyrokseniittisista, oliviini pyrokseniittisista ja peridotiittisista yksiköistä, jotka tunkeutuivat kerrosmyötäisesti Sodankylä-ryhmän tuffin ja epiklastisen kerrostuman väliin. Entuudestaan tuntematon ...